Pengaruh Kepemimpinan Transformasional, Disiplin Preventif, dan Kompensasi Finansial Terhadap Kinerja Karyawan Pada PT. XX - Febriyanti, Rada; Sumartik, Sumartik; Sriyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to ascertain the direct effects of financial compensation, transformational leadership, and preventative discipline on employee performance at PT. Xx. Both primary and secondary data are used in this kind of quantitative study. With a total of 120 employees, the researcher employed saturation sampling, a non-probability sampling approach. A Likert scale, with a range of 1 to 5, was used to measure the data gathering strategy in this study. Data was gathered through observations, interviews, and questionnaires. The study's findings demonstrates that employee performance is directly impacted by transformational leadership. Employee performance is directly impacted by preventive discipline. Employee performance is directly impacted by transformational leadership. Employee performance is directly impacted by financial pay.